MOTIVASI DAN MAKNA LATIHAN KEJIWAAN PENGHAYAT PPK SUBUD CABANG YOGYAKARTA - Mrs Watini (Religi: Jurnal Studi Agama-agama, 2014)
Religion is basically a complete guidance for mankind. Nevertheless, many of religious people are not satisfied with their own religions due to the lack of formal religion for addressing inner spiritual dimension. They look for, therefore, alternative paths for fulfilling their spiritual thirstiness. SUBUD (Susila Budi Darma) is one of  alternative spiritual-belief  systems in Yogyakarta considered as able to provide spiritual answers. Through psychological-phenomenological approach this study examines motive and meaning of the spiritual practices in the SUBUD.